Kerangka Konseptual Budaya Organisasi Syariah Berbasis Amanah untuk Penguatan Etika Kerja Pegawai Yayasan Keagamaan - Redo Pratama Harista; Himyar Pasrizal (MABIS Jurnal Manajemen Bisnis Syariah, 2026)
This article aims to formulate a conceptual framework of sharia organizational culture based on amanah to strengthen the work ethic of employees in religious foundations. The study employs a qualitative literature review design by placing the treatise Kaifa Yu’addi al-Muwazhzhof al-Amanah as the primary source, then relating it to Qur’anic and hadith-based discussions on amanah as well as to studies on Islamic organizational culture and Islamic work ethics. The analysis shows that amanah in the Qur’anic perspective cannot be reduced to personal honesty alone, but includes obedience, trustworthiness, responsibility, and keeping promises, which are closely related to the relationship between humans and Allah, fellow humans, and themselves. The treatise on becoming a trustworthy employee further operationalizes amanah into concrete work behavior, such as safeguarding working time, avoiding betrayal of position, rejecting bribery, and carrying out duties sincerely and professionally. The study concludes that amanah can be positioned as the core value of sharia organizational culture, which is internalized through leadership, organizational norms, and HR practices, and subsequently strengthens employee work ethic in religious foundations. This framework may serve as a theoretical basis for further empirical studies and as a practical reference for foundation management.